2011
DOI: 10.1002/jhm.860
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of a point‐based VTE risk assessment tool in the hands of medical residents

Abstract: BACKGROUND:Venous thromboembolic events (VTE) are a significant cause of mortality in hospitalized medical and surgical patients. Despite recommendations and guidelines, current evidence demonstrates that VTE prophylaxis remains underutilized in at‐risk patients. The process of providing VTE prophylaxis begins with assessing each patient's VTE risk. Using an individualized, point‐based protocol in the assessment process is a complex task, and might contribute to variability in VTE prescribing behavior. There a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…There are several caveats to those considering the use of these more complex point‐based models. Complex point‐based RAM suffer from poor interobserver agreement . They have also had limited ability to exclude low‐risk patients from prophylaxis in validation studies, and have not been tested extensively in medical populations.…”
Section: Choosing a Vte Rammentioning
confidence: 99%
See 1 more Smart Citation
“…There are several caveats to those considering the use of these more complex point‐based models. Complex point‐based RAM suffer from poor interobserver agreement . They have also had limited ability to exclude low‐risk patients from prophylaxis in validation studies, and have not been tested extensively in medical populations.…”
Section: Choosing a Vte Rammentioning
confidence: 99%
“…Complex point-based RAM suffer from poor interobserver agreement. 32 They have also had limited ability to exclude low-risk patients from prophylaxis in validation studies, 33 and have not been tested extensively in medical populations. Although AT9 considers the Caprini RAM relatively easy to use, 9 our experience in collaboratives suggests that for many hospitals, the model is too complex to be used reliably.…”
Section: Approach 3: Buckets Of Riskmentioning
confidence: 99%
“…4,5 At many medical institutions, residents perform the majority of admission risk assessments and order VTE prophylaxis; despite few studies showing if residents can reliably apply a VTE risk assessment tool. 15,16 In the present study, appropriate VTE prophylaxis was given in only 18.75% of low risk, 29.17% of moderate risk and 65.51% of high risk patients. These data suggest that those patients with high risk were easily picked up and given appropriate VTE prophylaxis whereas there is a tendency of under prophylaxis in medium and low risk individuals.…”
Section: A Each Risk Factor Carries 1 Pointmentioning
confidence: 75%
“…We compared previously published inter-rater reliability and adherence data to new inter-rater reliability and adherence data within the same residency program. We found that early in the academic year, and without any exposure to the risk assessment tool, our residents showed variation in risk assessment, VTE plan, and protocol adherence [9]. One year after integrating a point-based prophylaxis tool, the inter-rater reliability remained largely unchanged, but that overall adherence improved.…”
Section: Discussionmentioning
confidence: 99%
“…However, residents perform the majority of admission risk assessments and order VTE prophylaxis; despite few studies showing if residents can reliably apply a VTE risk assessment tool [9, 10]. Reliable application of risk assessment tools can reduce practice variation [11].…”
Section: Introductionmentioning
confidence: 99%